Robot-Assisted Kyphoplasty Improves Clinical and Radiological Features Better Than Fluoroscopy-Assisted Kyphoplasty in the Treatment of Vertebral Compression Fractures: A Meta-Analysis - Yu, Hongwei; Luo, Gan; Yu, Bin; Sun, Tianwei; Tang, Qiong; Jia, Yutao (Frontiers in Surgery, 2022)
Abstract Purpose: This meta-analysis aimed to determine whether patients treated with robot-assisted kyphoplasty for vertebral compression fractures have superior clinical and radiographic improvement than those treated with fluoroscopy. Methods: The protocol for this review was registered on the International Platform of Registered Systematic Review and Meta-analysis Protocols database with the registration number INPLASY202250106 and DOI number 10.37766/inplasy2022.5.0106. A comprehensive search of the PubMed, Embase, Cochrane Library, Science Direct, and CNKI (China National Knowledge Infrastructure) databases was conducted to find randomized control trials (RCTs) or observational cohort studies that compared robotic-assisted kyphoplasty (RA-kyphoplasty) with fluoroscopy-assisted kyphoplasty (FA-kyphoplasty) in treating vertebral compression fractures. Preoperative, postoperative, and final follow-up data on vertebral height (VH), vertebral kyphosis angle (VKA), visual analog scale (VAS) for back pain, and cement leakage rates were collected from eligible studies for meta-analysis. Patients were divided into RA and FA groups depending on whether the operation was robotically or fluoroscopically guided. Results: We included 6 cohort studies with 491 patients and 633 vertebrae. The results of the meta-analysis showed that the RA group had a higher VH than the FA group at both postoperation (p<0.001) and final follow-up (p<0.001); the VKA in the RA group was lower than that in the FA group at postoperation (p<0.001) and final follow-up (p<0.001); the back pain VAS scores were lower in the RA group than in the FA group at postoperation (p=0.01) and final follow-up (p=0.03); and the cement leakage rates in the RA group were lower than those in the FA group (p<0.001). Conclusion: This meta-analysis demonstrated that RA-kyphoplasty outperformed FA-kyphoplasty in vertebral height restoration, kyphosis angle correction, VAS score reduction for back pain, and lower cement leakage rates in the treatment of vertebral compression fractures.